Angel dream [compact disc] : songs from the motion picture She's the one - Petty, Tom (Warner Bros., 2021)
"To celebrate the 25th anniversary of the release of She's the One, the album has been re-imagined as Angel Dream--and is the final chapter of the audio releases relating to Petty's masterpiece Wildflowers. The original release of She's the One included several songs that were written during the Wildflowers period, but were not selected for inclusion on that album. The recent release of Wildflowers and All the Rest included these songs, and therefore they are not duplicated here. In their place, four previously unreleased songs (also written during this period) are added to this album"--Tom Petty website.